2023
DOI: 10.1038/s41598-022-25989-3
|View full text |Cite
|
Sign up to set email alerts
|

Human-mediated dispersal drives the spread of the spotted lanternfly (Lycorma delicatula)

Abstract: The spotted lanternfly (Lycorma delicatula) is a novel invasive insect from Asia now established and spreading throughout the United States. This species is of particular concern given its ability to decimate important crops such as grapes, fruit trees, as well as native hardwood trees. Since its initial detection in Berks County, Pennsylvania in 2014, spotted lanternfly infestations have been detected in 130 counties (87 under quarantine) within Connecticut, Delaware, Indiana, Maryland, New Jersey, New York, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…The G1 findings in 2021–2022 align with previous train-mediated SLF dispersal projections (Jones et al 2022, Ladin et al 2023). The findings on the university S4 site, however, do not align well with train-mediated dispersal, due to its 1.25 km distance from the nearest rail-line, exceeding the expected unaided dispersal range of the SLF (Wolfin et al 2019).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The G1 findings in 2021–2022 align with previous train-mediated SLF dispersal projections (Jones et al 2022, Ladin et al 2023). The findings on the university S4 site, however, do not align well with train-mediated dispersal, due to its 1.25 km distance from the nearest rail-line, exceeding the expected unaided dispersal range of the SLF (Wolfin et al 2019).…”
Section: Discussionsupporting
confidence: 86%
“…This suggests that the SLF at S4 likely dispersed to this woodlot by other means. This dispersal may have been aided by personal vehicles (as previously predicted; Jones et al 2022, Ladin et al 2023), as a number of out of state employees commute regularly to the university campus, including from quarantined Pennsylvania counties. However, S4 is relatively far away from campus commuter lots, and a number of survey sites adjacent to staff parking spaces on the campus (e.g., S1, S2, and S3) each had 0 SLF recordings across both sampling years despite the comparable density of preferred hosts.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Data from field trap captures have shown that L. delicatula are consistently present on J. nigra throughout the insect's development, but adults are in much lower numbers than nymphs when compared with A. altissima (Nixon et al 2023a). As studies have shown, L. delicatula can complete their development and reproduce in field cages containing the hardwood trees S. babylonica, A. saccharinum , and B. nigra (Uyi et al 2020, 2021); the suitability of these common wild hosts, including J. nigra , allows for greater spread and establishment of L. delicatula throughout the Eastern United States than can be predicted by assuming establishment only occurs when A. altissima is present (Ladin et al 2023). While certain deciduous hardwoods and woody ornamentals have been shown to be less suitable for L. delicatula , we do not know the reason.…”
Section: Discussionmentioning
confidence: 99%
“…Suitability of both wild and cultivated host plants, combined with emerging information on temperature limits and L. delicatula diapause (Keena and Nielsen 2021, Kreitman et al 2021, Nixon et al 2022a), can be used to inform predictive models on the spread of this invasive species (Jung et al 2017, Wakie et al 2020, Huron et al 2022). However, with the capacity for human-assisted transport (Ladin et al 2023) and the prevalence of A. altissima across the United States, eradication will continue to be difficult (Urban and Leach 2023). Spread and establishment can be slowed by concentrating management efforts on key hosts such as A. altissima , J. nigra , and V. vinifera .…”
Section: Discussionmentioning
confidence: 99%